Microsecond molecular dynamics studies of cholesterol-mediated myelin sheath degeneration in early Alzheimer's disease. Issue 1 (8th December 2021) - Gupta, Mayuri; Weaver, Donald F.
Abstract : Extensive microsecond MD simulations were performed for heterogeneous reference membranes and physiologically relevant model myelin sheath membrane with systematically varied cholesterol composition to understand early Alzheimer's disease pathology. Abstract : Cholesterol-mediated perturbations of membrane structural integrity are key early events in the molecular pathogenesis of Alzheimer's disease (AD). In AD, protein misfolding (proteopathy) and pro-inflammatory conditions (immunopathy) culminate in neuronal death, a process enabled by altered membrane biophysical properties which render neurons more susceptible to proteopathic and immunopathic cytotoxicities. Since cholesterol is a principal neuronal membrane lipid, normal cholesterol homeostasis is central to membrane health; also, since increased cholesterol composition is especially present in neuronal myelin sheath ( i.e. brain "white matter"), recent studies have not surprisingly revealed that white matter atrophy precedes the conventional biomarkers of AD (amyloid plaques, tau tangles). Employing extensive microsecond all-atom molecular dynamics simulations, we investigated biophysical and mechanical properties of myelin sheath membrane as a function of cholesterol mole fraction ( χ CHL ). Impaired χ CHL modulates multiple bilayer properties, including surface area per lipid (APL), chain order, number and mass density profiles, area compressibility and bending moduli, bilayer thickness, lipid tilt angles, H-bonding interactions and tail interdigitation. The increased orientational ordering of both palmitoyl and oleoyl chains in model healthy myelin sheath (HMS) membranes illustrates the condensing effect of cholesterol. With an increase in χ CHL, number density profiles of water tend to attain bulk water number density more quickly, indicating shrinkage in the interfacial region with increasing χ CHL . The average tilt value is 11.5° for the C10–C13 angle in cholesterol and 64.2° for the P–N angle in POPC lipids in HMS. These calculations provide a molecular-level understanding of myelin sheath susceptibility to pathology as an early event in the pathogenesis of AD.